5-HT4 receptor agonists treatment reduces tau pathology and behavioral deficit in the PS19 mouse model of tauopathy - Jiang, Shan; Sydney, Eric J.; Runyan, Avery M.; Serpe, Rossana; Srikanth, Malavika; Figueroa, Helen Y.; Yang, Mu; Myeku, Natura (Frontiers in Cellular Neuroscience, 2024)
Accumulation of tau in synapses in the early stages of Alzheimer's disease (AD) has been shown to cause synaptic damage, synaptic loss, and the spread of tau pathology through trans synaptically connected neurons. Moreover, synaptic loss correlates with a decline in cognitive function, providing an opportunity to investigate therapeutic strategies to target synapses and synaptic tau to rescue or prevent cognitive decline in AD. One of the promising synaptic targets is the 5-HT4 serotonergic receptor present postsynaptically in the brain structures involved in the memory processes. 5-HT4R stimulation exerts synaptogenic and pro-cognitive effects involving synapse-to-nucleus signaling essential for synaptic plasticity. However, it is not known whether 5-HT4R activation has a therapeutic effect on tau pathology.The goal of this study was to investigate the impact of chronic stimulation of 5-HT4R by two agonists, prucalopride and RS 67333, in PS19 mice, a model of tauopathy. We utilized gradient assays to isolate pre-and post-synaptic compartments, followed by biochemical analyses for tau species and ubiquitinated proteins in the synaptic compartments and total brain tissue. Next, we performed kinetic assays to test the proteasome's hydrolysis capacity in treatment conditions. Moreover, behavioral tests such as the open field and non-maternal nest-building tests were used to evaluate anxiety-like behaviors and hippocampal-related cognitive functioning in the treatment paradigm.Our results show that 5-HT4R agonism reduced tauopathy, reduced synaptic tau, increased proteasome activity, and improved cognitive functioning in PS19 mice. Our data suggest that enhanced proteasome activity by synaptic mediated signaling leads to the enhanced turnover of tau initially within synapses where the receptors are localized, and over time, the treatment attenuated the accumulation of tau aggregation and improved cognitive functioning of the PS19 mice.Therefore, stimulation of 5-HT4R offers a promising therapy to rescue synapses from the accumulation of toxic synaptic tau, evident in the early stages of AD.